Myxoma of the left atrium presenting as repeated cerebrovascular disorders. - Serrano, A; Machado, J; Gonçalves, L P; Proença, R (Acta Médica Portuguesa, 1994)
Infarction of the central nervous system secondary to embolism from a left atrial myxoma is a recognized phenomenon. However, a myxoma as the source of an embolus may be overlooked, if, during the evaluation of a patient with a stroke of unknown etiology, an index of suspicion is not present. We report a case of a 57-year old woman presenting three episodes of cerebral infarction always in the same brain territory, suggesting a carotid pathology. The physical examination of the patient only showed a loud S1 with no other sounds and neurologic alterations, namely, right hemiparesia and aphasia. Diagnosis was made by two-dimensional echocardiography and better delineation was obtained by magnetic resonance imaging (MRI). The patient subsequently received a successful ressection of the myxoma. Eighteen months later the patient was well.